2017
DOI: 10.1038/srep45622
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-functionalized Decalcified Bone Matrix Scaffolds with Enhanced Pro-angiogenic and Pro-bone Regeneration Activities

Abstract: Vascularization is crucial for bone regeneration after the transplantation of tissue-engineered bone grafts in the clinical setting. Growing evidence suggests that mesenchymal stem cell (MSC)-derived extracellular vesicles (EVs) are potently pro-angiogenic both in vitro and in vivo. In the current study, we fabricated a novel EV-functionalized scaffold with enhanced pro-angiogenic and pro-bone regeneration activities by coating decalcified bone matrix (DBM) with MSC-derived EVs. EVs were harvested from rat bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 41 publications
(57 reference statements)
3
130
1
Order By: Relevance
“…Many of the proteins identified in this paper have also been identified in a proteomic analysis of osteoblast released EVs [31, 52]. A previous in vivo study has suggested a role for EVs in systemic signalling, demonstrating altered miRNA expression in EVs isolated from the plasma of osteocyte ablated mice and wild-type mice [24], while other studies have demonstrated the potential for EVs in therapeutics to enhance osteogenic gene expression [53], the use of drug loaded EVs for osteoporosis therapies [27], and the use of EVs for functionalisation of TE scaffolds to enhance bone regeneration [54, 55]. In addition to osteocyte derived MAEVs and the contents driving MSC osteogenesis, MAEVs may also act as sites for mineral nucleation, as has previously been demonstrated in osteoblast EVs [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the proteins identified in this paper have also been identified in a proteomic analysis of osteoblast released EVs [31, 52]. A previous in vivo study has suggested a role for EVs in systemic signalling, demonstrating altered miRNA expression in EVs isolated from the plasma of osteocyte ablated mice and wild-type mice [24], while other studies have demonstrated the potential for EVs in therapeutics to enhance osteogenic gene expression [53], the use of drug loaded EVs for osteoporosis therapies [27], and the use of EVs for functionalisation of TE scaffolds to enhance bone regeneration [54, 55]. In addition to osteocyte derived MAEVs and the contents driving MSC osteogenesis, MAEVs may also act as sites for mineral nucleation, as has previously been demonstrated in osteoblast EVs [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…For each section, three images were captured for quantitative analysis of the positive staining of CD31. Image‐Pro Plus 6.0 software was used to evaluate the mean vessel density with the calculation of positively stained vessel area per unit area …”
Section: Methodsmentioning
confidence: 99%
“…Image-Pro Plus 6.0 software was used to evaluate the mean vessel density with the calculation of positively stained vessel area per unit area. 24…”
Section: Micro-ctmentioning
confidence: 99%
“…To date, MSC-derived EVs have been widely used to functionalize a variety of scaffold structures due to their proangiogenic properties. Xie et al coated decalcified bone matrix (DBM) with bone marrow-derived MSC EVs using fibronectin as the immobilizing agent [54].…”
Section: Engineered Scaffolds and Surfacesmentioning
confidence: 99%